Optimization of Methylene Blue Dye Adsorption in Fixed Bed Column Packed with Tea Waste via Response Surface Methodology - Novi Sylvia; Rozanna Dewi; Zulnazri Zulnazri; Hendi Setiawan; Dinda Humaira; Mutia Reza (Jurnal Kimia Sains dan Aplikasi, 2023)
Tea waste is a low-cost alternative material for making adsorbent to remove methylene blue from synthetic dye wastewater perpetually. Optimization of the adsorbent process utilized Response Surface Methodology (RSM) and a continuously operating system in a fixed bed column. The independent variables in the research are X1 (bed height), X2 (contact time), and X3 (flow rate). The dependent variable is Y1 (removal efficiency) with a matrix design by Box-Behnken. The optimum condition of methylene blue (MB) B removal was found at X1=16 cm, X2=90 min, and X3=4 L/min with an adsorption efficiency of 90.45%. After the activation and adsorption of MB dye, the complete FTIR spectrum shows a distinct peak at 2933.7 cm-1. The results of the EDX analysis performed on tea waste reveal the presence of nitrogen (element N) following the adsorption process. This observation strongly suggests that the tea waste has effectively absorbed MB, as nitrogen is a constituent element found in the molecular structure of MB.